THE INFLUENCE OF FINANCIAL LITERACY AND PERCEPTION OF QANUN TOWARD SAVING BEHAVIOR ACEHNESE PEOPLE - Fakhrina Fadhli; Irni Rahmayani Johan (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
All conventional banks in Aceh Province have converted to Islamic banks since the enactment of Qanun (Regional Regulation) Number 11 of 2018, so people need to adapt to several changes in banking transactions, including saving. The purpose of this study is to analyze the effect of financial literacy and the perception of Qanun on the saving behavior of the people of Aceh. This research uses a cross sectional study design. The data used are primary data and secondary data. Sampling was done by convenience with the sample is a community that meets the requirements of the last education at least high school / equivalent, have a savings account, and domiciled in Banda Aceh or Aceh Besar. The number of respondents obtained in this study was 217 people. Interviews were also conducted for several question items to six informants. The data were processed using Microsoft Excel and statistical testing was conducted with the Statistical Package for Social Sciences (SPSS). The results showed that the respondents' financial literacy level was in the well literate category, perceptions related to Qanun were at a moderate level, and saving behavior was still low. There is a significant positive relationship between the dimensions of financial attitudes, financial behavior, and perceptions of Qanun on saving behavior. The results of the regression test analysis show that financial behavior and perceptions of Qanun have a significant positive effect on saving behavior. This research is expected to be an input for policy makers, especially related to the perception of Qanun and saving behavior.